Program Darling (Tadarus Keliling) Sebagai Strategi Peningkatan Kemampuan Public Speaking Santri - Yada, Kholifatin Maha; Mumtahana, Lusia (Andragogi: Jurnal Pendidikan dan Pembelajaran, 2024)
The study on improving the public speaking skills of T.P.Q. Muhammadiyah Menongo Sukodadi Lamongan students uses a qualitative research method with a descriptive approach. This research aims to describe the "Darling" program at T.P.Q. Muhammadiyah Menongo Sukodadi Lamongan explains the implementation of the Darling (Tadarus Keliling) program as a strategy to enhance the public speaking skills of the students and analyze the supporting and inhibiting factors of the Darling (Tadarus Keliling) program. The results of this study are as follows: 1) Darling (Tadarus Keliling) is a program designed to train responsibility and public speaking, strengthen silaturrahim (social bonds), and encourage the regular recitation of the Al-Qur’an. 2) Darling is conducted once every two weeks on Tuesdays at 14:00 W.I.B. at students’ homes, with activities aimed at improving their public speaking skills and increasing their confidence in appearing in front of others after participating in the program. 3) Supporting factors include the honing of public speaking skills and the establishment of silaturrahim. Inhibiting factors include challenges related to time, conditions, and unpredictable weather.